Fundamental apparent plastic anisotropy of duplex embossed aluminum sheet. (November 2019) - Liu, Wuyang; Iizuka, Takashi
Highlights: Intrinsic plastic deformation behavior for duplex embossed sheets was investigated. The effect of anisotropies resulting from crystal texture and embossing pattern with changing embossing degree was investigated. An intrinsic "V"-shape relationship between apparent r-value and emboss based direction was clarified. Apparent plastic anisotropy emerges as a superposition of these two anisotropies and varies with embossing height and angle deviation. A simple superposition model of two anisotropies in different scales was proposed, and the effectiveness of the model was confirmed. Based on this model, the optimum embossing conditions for the minimum in-plane anisotropy were found. Abstract: The duplex embossing process is an advanced sheet metal forming process to enhance the mechanical and functional characteristics of sheet metal. Especially for the yield strength, stiffness, energy absorption, heat radiation and so on. When sheet metal is subjected to the embossing process, a new quasi-uniform "apparent" macroscopic property will be given by embossing periodic pattern. Embossed sheet is also thought as one of the generic tailored blanks. As embossed sheets are getting applied more and more in industry, it would be very important to clarify this fundamental apparent plastic anisotropy of such sheet metal with a periodic arrangement. In this study, uni-axial tensile tests of duplex embossed sheets with different embossing conditions were conducted experimentally and analytically respectively. At first, apparent Lankford values were measured, and effects derived from crystal texture and embossing pattern were investigated. And variations of these effects with degree of embossing process were also investigated. From these results, it is thought that the apparent plastic anisotropy of embossed sheet emerges as a superposition of these two anisotropies and varies with embossing height and angle deviation. Finally, based on this consideration, a simple superposition model of two anisotropies in different scales was proposed, and the effectiveness of the model was also discussed and confirmed.